Floristic Inventory and Diversity Assessment at Two Locations along the Shores of Cape Coast, Ghana - Gertrude Lucky Aku Dali; Sethiler Arthur; Paul Kwame Essandoh (Scientifica)
Coastal vegetation plays significant roles such as stabilization of the surface against wind and erosion, and provision of critical terrestrial and aquatic habitats for organisms. Floristic studies serve as a way of monitoring and evaluating the health of ecosystems. Currently, information on the floristic composition and diversity along the shoreline of Cape Coast is scanty. The study was aimed at assessing the impacts of anthropogenic activities on plant biodiversity along the shoreline of Cape Coast, Ghana. Thus, the study analysed the biodiversity of plants at the Hutchland beach (a disturbed area) and the Asasse Pa beach (a fairly undisturbed area). It was hypothesised that the Asasse Pa beach had a higher species diversity than the Hutchland beach. An inventory was made of all plant species found at both locations. A belt transect method was used for the ecological study, involving the use of a 1 m2 quadrat. All the plants that were found in each quadrat were identified, and the species and number of individuals of each species were counted—this information was used in the determination of the ecological parameters of the species and the locations. Parameters between the two locations were compared with a t-test, whereas variations in the distribution of the species were determined with principal components analysis (PCA), using Minitab and R statistical software, respectively. A total of 50 plant species belonging to 48 genera and 23 families were inventoried along the shoreline. The family Poaceae had the highest number of species, 10. The Asasse Pa beach had a higher species diversity and evenness of 2.84 and 0.84, respectively, whereas the Hutchland beach had a lower species diversity and evenness of 2.44 and 0.75, respectively. Anthropogenic activities at the Hutchland beach might have accounted for the lower species diversity and evenness there. The study therefore recommends periodic monitoring of coastal vegetation also law enforcement on coastal resources.